2017
DOI: 10.3390/ijerph14111288
|View full text |Cite
|
Sign up to set email alerts
|

Health in All Policies in South Australia—Did It Promote and Enact an Equity Perspective?

Abstract: Mobilising cross-sectoral action is helpful in addressing the range of social determinants that contribute to health inequities. The South Australian Health in All Policies (SA HiAP) approach was implemented from 2007 to stimulate cross-sector policy activity to address the social determinants of health to improve population wellbeing and reduce health inequities. This paper presents selected findings from a five year multi-methods research study of the SA HiAP approach and draws on data collected during inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 54 publications
0
40
0
Order By: Relevance
“…176,177 This is about working smarter; and has significant potential to save government expenditure over the longer-term. [178][179][180] In addition, to required action on the social determinants of health already noted above, there is also a need to influence environments through improved urban planning processes that address gender-specific needs. For example, numerous countries have turned to temporary urban design measures to quickly create new forms of space for their citizens that enable safe physical activity and commuting within cities.…”
Section: Poverty Gender and The Social Determinants Of Men's Healthmentioning
confidence: 99%
“…176,177 This is about working smarter; and has significant potential to save government expenditure over the longer-term. [178][179][180] In addition, to required action on the social determinants of health already noted above, there is also a need to influence environments through improved urban planning processes that address gender-specific needs. For example, numerous countries have turned to temporary urban design measures to quickly create new forms of space for their citizens that enable safe physical activity and commuting within cities.…”
Section: Poverty Gender and The Social Determinants Of Men's Healthmentioning
confidence: 99%
“…19,20 Van Eyk et al indicated that HiAP in South Australia had dual goals; the facilitation of joined-up government for the common benefit of all citizens and consideration of the social determinants of health and inequities via cross-sectoral policies. 21 The southern Australian experience in implementing HiAP shows that a focus on intersectoral collaboration and participation are requirements for implementation. In a report on the details of implementing an HiAP model to address regional migration in Adelaide, Australia in 2010, a tool entitled "Health Lens Analysis" was introduced, with the aim of maximizing health and wellbeing.…”
Section: Systematic Development Of Intersectoral Collaborationmentioning
confidence: 99%
“…Inspired by new institutionalism, we regard organisations and their agents to be dependent on their institutional environment and on gaining legitimacy not only to succeed economically but also to survive [8][9][10]. To examine HiAP, other scholars have used institutional perspectives, such as path dependency and rationalised myth [11][12], institutional logics [13] and translation of organisational ideas [14][15]. By contrast, studies that apply a legitimacy perspective have been difficult to find.…”
Section: Theoretical Perspectivementioning
confidence: 99%